Epidemiological Study of Pasteurella Multocida Isolated from Sheep - Al-Janabi, Baqer Hussein Jejan; Ajeel, Hameedah Hamzah (American Journal of Biology and Natural Sciences, 2026)
The objectives of this study were to determine the epidemiology and laboratory diagnosis of pneumonic pasteurellosis due to Pasteurella multocida in sheep at Al-Qasim, Babylon Governorate. A total of 168 samples were obtained from sheep that had exhibited respiratory signs, comprising 80 nasal swabs, 70 oral swabs, and 18 lung tissues from slaughtered suspected pneumonia cases. Isolates were cultured on several selective and differential media, and bacterial identification was done with the VITEK 2 system. The results showed that P. multocida was the predominant isolate (41.10%), followed by Klebsiella (19.64%), Staphylococcus (15.47%), and E. coli (9.52%). Antibiotic susceptibility testing revealed high sensitivity to amoxicillin (87%), ceftiofur (84%), and florfenicol (76%), whereas high resistance was recorded against penicillin G (80%), meropenem (76%), and gentamicin (73%). A significantly higher prevalence was observed in males (47.91%) than females (38.33%) and in the 1–3-year age group (45.79%) compared to younger animals (32.78%). These findings highlight the major role of P. multocida in ovine respiratory infections and emphasize the importance of continuous antimicrobial monitoring and rational antibiotic use to control multidrug-resistant strains in livestock populations.